MUSCLE TISSUE: STRUCTURE, FUNCTION, BIOLOGY, AND MEDICAL SIGNIFICANCE - Qosimova Mohlaroyim Bahromjon kizi; Mukhammadjonova Dilyoraxon Khusanjon kizi (TADQIQOTLAR, 2026)
Abstract:  This article provides an in-depth analysis of muscle tissue, exploring its  structure,  types,  physiological  and  biochemical  processes,  regeneration mechanisms,  and  clinical  relevance.  It  covers  the  development  and  functioning  of skeletal,  cardiac,  and  smooth  muscle,  assessing  both  their  similarities  and  distinct features. Emphasis is placed upon the role of cellular and molecular mechanisms in muscle adaptation, maintenance, and repair, as well as on current and potential medical applications in muscle-related disease and injury.